MODERN METHODS OF TREATMENT OF RECURRENT UNRESECTABLE SQUAMOUS CELL CARCINOMA OF LARYNX (LITERATURE REVIEW) - V. A. Rozhnov; V. G. Andreev; K. B. Gordon; I. A. Gulidov; E. D. Akki (Сибирский онкологический журнал)
The literature review presents the modern methods of treatment of inoperable recurrent squamous cell cancer of the larynx. The application of radiation and chemotherapy.